Exploring nurses’ experiences in pressure sore care in long-term care facilities - Hyung-Ju Na; Sung-Hee Yoo; Young-Ran Kweon (International Journal of Qualitative Studies on Health & Well-Being, 2024)
Background This study uses an interpretive description approach to explore nurses’ experiences with pressure sore care in long-term care facilities, highlighting the complexity of their encounters. Methods 10 experienced nurses from South Korean small to medium-sized hospitals were chosen via purposive sampling for interviews. Data analysis utilized Braun and Clarke’s reflexive thematic analysis. Results The study’s findings collectively reflect the intricate journey of nurses in Long-term care facilities as they grapple with the challenges of pressure sore care. These nurses transform their perception of pressure sores, encountering a dynamic shift in their understanding. They face multifaceted challenges in providing optimal care, marked by resource constraints and the absence of standardized guidelines. Emotionally, they navigate a complex terrain of sentiments, oscillating between feelings of accomplishment and helplessness. Despite these hurdles, they persistently strive for excellence in pressure sore nursing, driven by an unwavering commitment to delivering the best possible care within the confines of their healthcare environment. Conclusion The study enhances understanding of pressure sore care in long-term facilities and suggests avenues for improving nursing practices and care quality through targeted interventions.